Thinking racial capitalism and black radicalism from Africa: An intellectual geography of Cedric Robinson's world-system. Issue 132 (June 2022) - Al-Bulushi, Yousuf
Highlights: Unpacks the specificity of racial capitalism & black radicalism in Cedric Robinson. Resituates these concepts in the intellectual geography of Africa. Grounds world-systems analysis in Africa and argues for a black world-systems. Synthesizes the four constituent elements of Robinsonian black radicalism. Draws from interviews, Robinson's archive, and previously uncirculated manuscripts. Abstract: Recent writing on race and capitalism in geography and related fields has taken much inspiration from the work of Cedric Robinson. Yet the specificity of his most important concepts—racial capitalism and black radicalism—remains somewhat underdeveloped in the conversations surrounding the resurgence of his work. This article conducts an intellectual geography of Robinson's interventions by identifying some of the key theoretical and geographical contexts in which his work intervenes. It places Africa at the center of his political and intellectual evolution, and explores the centrality of the continent to his early work from the 1960s through the 1990s. It argues that Robinson was shaped by a close engagement with world-systems scholars, who were in turn also markedly informed by the study of Africa and their time spent on the continent. The article conducts an exegetical study of Robinson's key texts, draws on interviews with his surviving partner, Elizabeth Robinson, and from ongoing archival work to explore the African roots of world-systems analysis and the relationship between Robinson's own ideas and debates concerning South Africa, Tanzania and Liberia. It concludes by offering a synthesis of four constituent elements in the Robinsonian black radical tradition.